Bioelectrochemistry : Design and Applications of Biomaterials - Aleksejeva, Olga;Barrière, Frédéric; Blum, Zoltan; Borsali, Redouane; Bouffier, Laurent; Cai, Wen-Rong; Cirovic, Stefan; Cosnier, Serge; Costa, Nazua L.; Dong, Shaojun; Etienne, Mathieu; Falk, Magnus; Flinois, Thomas; et al. (De Gruyter, 2019)
Bioelectrochemistry is a fast growing field linking together electrochemistry, biochemistry, medicinal chemistry and analytical chemistry. The current book outlines the recent progress in the area and the applications in biological materials design and bioenergy, covering in particular biosensors, bioelectronic devices, biofuel cells, biodegradable batteries and biomolecule-based computing.